The Effect of Card Game on Students Speaking Achievement at Madrasah Aliyah Karae - Sini, Wa; Nurindah, Nurindah; Siam, Siam (Journal of Teaching of English, 2021)
The objective of this research is to find out the effect of using card game on students’ speaking achievement at MA Karae. It was conducted in the pre-experimental research design. The population of this research was the students of class X IPA MA Karae which consists of two classes with 53 students, while the subject of this research is the class X science program consisting of 28 students. The research data were collected by giving pretest and post-test to students in the form of oral tests related to the topic of personal introductory expressions, intentions and favorite places. Data were analyzed using SPSS 16.0 using (descriptive analysis and inferencial statistic). Meanwhile, to test the hypothesis, the researcher used a t-test (paired sample t-test) which was calculated through SPSS 16.0. The result shows that there is a significant effect of card playing technique on students' speaking achievement in the first year MA Karae students. It also shows that the use of this technique can improve the accuracy and fluency of students' speaking. It can be seen from the average post-test score is 53.21, while the average score of the pre-test is 29.28. To prove the hypothesis, the researcher concludes by comparing the Sig (2 tailed) value with the significance value α. This shows that the Sig (2 tailed) value was 0,000 while the significance value α is 0.05. So, it can be concluded that the Sig (2 tailed) value is lower than the significance value α (0,000 <0.05). In other words, (H1) is accepted. It means that there is a significant influence of the card game technique on students 'speaking ability in the first year of the MA Karae.